Effect of nano-reduction on properties of β-glucan and its use as encapsulating agent for release of α-tocopherol. (October 2020) - Ashraf, Zanoor ul; Shah, Asima; Gani, Adil; Masoodi, F.A.; Noor, Nairah
Abstract: In this work, nanoreduction of β-glucan by emulsion diffusion method and its effect on structural, rheological and antioxidant properties were studied. Dynamic light scattering confirmed the formation of the β-glucan particles in the nanosize range with an average size of 78.5 nm. FTIR revealed a difference in the intensity of peaks between β-glucan nanoparticles and β-glucan. Rheological analysis of both gels showed Newtonian behaviour, however, nanoreduction of β-glucan decreased the viscosity of the gel. DPPH scavenging activity, reducing power and metal chelating activity were performed which displayed that antioxidant activity of β-glucan nanoparticles was significantly higher (P < 0.05) than β-glucan. Furthermore, β-glucan nanoparticles offered more protection to DNA against the oxidative damage caused by (-OH) radicals. Also, β-glucan nanoparticles and β-glucan were used as wall material for encapsulation of α-tocopherol and its in-vitro release behavior was studied during its transit in the GI tract. The release of α-tocopherol from β-glucan was observed higher in β-glucan nanoparticles than β-glucan.